Viability of Peranakan Etawah Liquid Semen Preserved in Tris Substituted with Various Energy Sources - Nurul Afzan Hilda Zakiya; A H Yanti; T R Setyawati (Indonesian Center for Animal Research and Development (ICARD), 2020)
The use of liquid semen for artificial insemination program of Etawah crossbreed goat (PE) is an alternative to replace frozen semen which is constrained by limited and expensive facilities. Production of liquid semen is faster than frozen semen, but the viability of liquid semen which preserved with a standard extender such as tris egg yolk is very short. The purpose of this study was to determine the viability of PE goat semen in egg yolk tris substituted with energy sources such as glucose, galactose, and mannose and to determine the most efficient energy source for semen preservation. This research was conducted from August to September 2018 at the Artificial Insemination Center in Lembang, West Java. This study was designed in a randomized block design (RBD) consist of three experimental groups divided into five groups. Fresh semen of PE goats were preserved using extender which energy source has been modified. Results showed that using glucose in PE goat semen extender produced the best motility among other groups (64.29 ± 9.2%). The highest viability was found in extender with fructose substitution (86.76 ± 2.3%). The longest viability of liquid semen was found in the extender with glucose substitution. It lasted for six days.